Multiple close-range geomatic techniques for the kinematic study of the La Paúl rock glacier, southern Pyrenees - Martínez Fernández, Adrián; Serrano Cañadas, Enrique; Sanjosé Blasco, José Juan de; Gómez Lende, Manuel; Sánchez Fernández, Manuel; Pisabarro Pérez, Alfonso; Atkinson, Alan David (Remote Sensing, 2023)
Producción Científica Rock glaciers are one of the most representative elements of mountain permafrost. Their study can contribute to modelling climate change and its effect on natural and anthropogenic environments. Therefore, it is crucial to understand the evolution and quantify the changes in these periglacial landforms at a global level. This study aims to present the monitoring work carried out on the Pyrenean rock glacier of La Paúl (42°39′40″N, 0°26′34″E) from 2013 to 2020, employing in situ geomatics techniques to determine the landform surface kinematics accurately. For this purpose, global navigation satellite systems (GNSS), terrestrial laser scanners (TLS), and unmanned aerial vehicles (UAV) photogrammetry techniques were used simultaneously to evaluate their compatibility in quantifying displacements. Based on 2D and 3D analyses, the results demonstrate the high surface activity of the rock glacier, with mean variations reaching 36 cm/year (GNSS) and a distribution of deformations that, although intensified on its western side, are present on the entire surface of La Paúl. This study uses state-of-the-art geomatics techniques to present dependable and updated quantitative data on a periglacial landform’s recent development in under-researched areas, such as the Pyrenean temperate high mountain. Ministerio de Economía, Industria y Competitividad - (projects CGL2015-68144-R and PID2020-113247RB-C21)